Estimation Of Andrographolide In Herbal Powder And Polyherbal Asava By HPTLC - MONIKA JADHAO (International Journal of Pharma and Bio Sciences, 2010)
Herbal powder and polyherbal formulation containing Andrographis peniculata were standardized and validated by high performance thin layer chromatographic method. Andrographolide in sample was identified and amount was estimated densitometrically. This method involves separation of compounds by TLC on pre-coated silica gel 60F 254 plates with the solvent system of benzene: ethyl acetate (5:5) and scanned using densitometric scanner in UV reflectance photomode at 220 nm. The linearity was observed in the range of 360ng-660 ng /spot. The andrographolide content of 237.2 µg/ 100 mg in powder and 41.80 mg/ 5ml. was observed in the test sample. The average percentage recovery value of 97.68 was obtained. The proposed method being precise and sensitive can be used for the detection, monitoring and quantification of andrographolide in Andrographis peniculata.